Perilaku Harian Keong Mas Pomacea canaliculata (Gastropoda: Ampullariidae): Daily Behaviour of the Golden Apple Snail Pomacea canaliculata (Gastropoda: Ampullariidae) - Savira, Aulia; Tambunan, Anggitha; Br. Purba, Desi Ariani; Rahman, Adam Ardian; Widarto, Tri Heru (Jurnal Sumberdaya Hayati, 2024)
P. canaliculata (Gastropoda: Ampullariidae) is a water snail that can be found in Indonesia. P. canaliculata is of concern to the community since it can become a pest in the agricultural sector and harm the community. This study aimed to determine the daily behaviour of P. canaliculata, which is located in Lake SDGs IPB University. The observations used the scan sampling method on 10 adult snails for 24 hours with three times repetitions. The results of this study indicate that P. canaliculata has four dominant behaviours: exploration, social interaction, immobile (fixed), and immobile (loose). In addition, P. canaliculata exhibits other behaviours such as siphoning out, feeding, mating, spawning, burying, exploration, and floating. Water temperature changes also influenced active and inactive behaviours. The observed activity of P. canaliculata snails was mostly carried out in water. P. canaliculata was more active in the dark phase (18.00-06.00) with water temperatures ranging from 29 to 32°C and more inactive in the light phase with water temperatures ranging from 28 to 29°C.